Stereoselective Multibond-Forming Process towards Functionalized Sulfamide-Containing Polycycles - Pantaine, Loïc; Laverny, Aragorn; Moreau, Xavier; Coeffard, Vincent; Greck, Christine (Synthesis, 2017)
Original polycyclic-containing sulfamide compounds have been synthesized through a domino aza-Michael/Michael/aldol condensation sequence. Resolution of the racemic bicyclic sulfamide starting materials to provide enantioenriched structures has also been investigated.
Keywords: sulfamides; aza-Michael addition; domino sequence; chiral resolution; polycycles